Repeated predictable or unpredictable stress: effects on cocaine-induced locomotion and cyclic AMP-dependent protein kinase activity - Araujo, APN; DeLucia, R.; Scavone, C.; Planeta, Cleopatra da Silva [UNESP] (Elsevier B.V., 2003)
Stressful experiences appear to have a strong influence on susceptibility to drug taking behavior. Cross-sensitization between stress and drug-induced locomotor response has been found. Locomotor response to novelty or cocaine (10 mg/kg, i.p.), cyclic AMP-dependent protein kinase (PKA) activity in the nucleus accumbens and basal corticosterone levels were evaluated in male adult rats exposed to acute and chronic predictable or unpredictable stress. Rats exposed to a 14-day predictable stress showed increased locomotor response to novelty and to cocaine, whereas rats exposed to chronic unpredictable stress demonstrated increased cyclic AMP-dependent PKA activity in the nucleus accumbens. Both predictable and unpredictable stress increased basal corticosterone plasma levels. These experiments demonstrated that stress-induced early cocaine sensitization depends on the stress regime and is apparently dissociated from stress-induced changes in cyclic AMP-dependent PKA activity and corticosterone levels. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: stress; cocaine; cyclic AMP-dependent protein kinase; corticosterone; nucleus accumbens; hypothalamus-pituitary-adrenal axis